Sustainability Enhancement in New Product Development - Darawong, Chonlatis (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
The objective of this article is to collect and present the information relating to sustainability enhancement in new product development. New product development is considered as the most important component for all businesses since they help manufacturing companies improve competitive advantage in all industries. The manufacturing companies not only put efforts to serve consumer needs, but they also have to get along with nearby society or community and environmental surroundings. Sustainable new product development can be generated in three ways; environmental, social, and economical. It can also be enhanced in every stage of new product life cycle, consisting of production stage, distributions stage, utilization stage, storage stage, and end of life stage. In addition, Top management should emphasize driving factors, including 1) cross-functional work 2) top management involvement 3) marketing planning, and 4) formalized processes.